Modified Generalized Exponential Distribution - Telee, Lal Babu Sah; Kumar, Vijay (Nepal Journal of Mathematical Sciences, 2023)
In this article, a new distribution having three called Modified Generalized Exponential Distribution is proposed. Important statistical properties of the proposed model like survival function, hazard rate function, the probability density function (PDF), the cumulative distribution function (CDF), quantile function, skewness, and kurtosis are discussed here. Least Square Estimation (LSE), Cramer- Von Mises (CVM) and Maximum Likelihood estimators (MLE) methods are used for estimation of parameters using R programming software. A data set is discussed and performed the goodness-of-fit to assess the applications of the proposed distribution. Various methods of model comparison and model validation are also used. The proposed model Modified Generalized Exponential Distribution is more applicable as compared to some existing probability model.